Sales Improvement through Web-based CRM Implementation - Gunawan, Aditya; Rahmadani, Nurul; Lubis, Iin Almeina (Sistemasi: Jurnal Sistem Informasi, 2024)
This research focuses on the implementation of Customer Relationship Management (CRM) at Gucci 3 Bunut Store, which is engaged in the leather products industry such as sandals, shoes, and others. The challenges faced by this store in managing sales, marketing, and customer service motivate the design of an effective and efficient CRM system. The CRM used in this research is an operational CRM that focuses on automating the sales and customer service processes. Qualitative research methods, through interviews and observations, were used to understand the needs of customers, employees, and related parties. CRM application development was carried out using the PHP programming language and MySQL database. The research objective was to improve the efficiency and convenience of customer interaction. The implementation results show the ease of obtaining product information and facilitating the ordering process. The implications include increased operational and service efficiency, potentially increasing customer loyalty. This research contributes to the understanding of CRM implementation in the retail sector, creates innovative solutions for Gucci 3 Bunut Store, and supports the improvement of service quality and customer satisfaction.